THE LINGUISTIC DIMENSION OF GENDER EQUALITY: A HUMAN RIGHTS PERSPECTIVE - V. Tolstokorova, Alissa (POLISSEMA – Revista de Letras do ISCAP, 2019)
The subject-matter of this essay is gender justice in language which, as I argue, may be achieved through the development of a gender-related approach to linguistic human rights. The last decades of the 20th century, globally marked by a “gender shift” in attitudes to language policy, gave impetus to the social movement for promoting linguistic gender equality. It was initiated in Western Europe and nowadays is moving eastwards, as ideas of gender democracy progress into developing countries. But, while in western societies gender discrimination through language, or linguistic sexism, was an issue of concern for over three decades, in developing countries efforts to promote gender justice in language are only in their infancy. My argument is that to promote gender justice in language internationally it is necessary to acknowledge the rights of women and men to equal representation of their gender in language and speech and, therefore, raise a question of linguistic rights of the sexes. My understanding is that the adoption of the Universal Declaration of Linguistic Rights in 1996 provided this opportunity to address the problem of gender justice in language as a human rights issue, specifically as a gender dimension of linguistic human rights.